Highly durable catalyst, its preparation method and application
Patent Information
- Application Number
- CN202611235492.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-16
AI Technical Summary
然而,现有的碳基阴极催化剂在长期运行过程中仍面临以下技术难题:第一,未修饰的碳材料表面活性位点有限,对2e-ORR的选择性较低,容易发生四电子路径生成水,导致H2O2产率不理想
1、本发明全程无需高温煅烧(最高温度不超过120℃),极大降低了制备能耗。同时,温和的条件完美保留了碳载体原有的孔道结构、高比表面积及本征导电性,避免了高温下碳骨架塌缩和导电性劣化的问题。
Smart Images

Figure CN122918608A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst materials technology, specifically relating to a high-durability catalyst, its preparation method and application. This method can significantly improve the selectivity, yield and durability of electrogenerated hydrogen peroxide. Background Technology
[0002] Hydrogen peroxide (H2O2) is a green oxidant with wide applications in environmental remediation, chemical synthesis, and disinfection. Currently, industrial production of H2O2 mainly relies on the anthraquinone process, but this process suffers from problems such as complex procedures, high energy consumption, generation of organic byproducts, and significant risks associated with the storage and transportation of high-concentration H2O2. Hydrogen peroxide can be produced through the two-electron oxygen reduction reaction (2e...). - ORR (Organic Regeneration) electrochemical synthesis of H2O2 is a clean and sustainable alternative that enables in-situ production of H2O2 under mild conditions.
[0003] The successful commercialization of H2O2 production via electrochemical methods hinges on the development of cathode catalysts with high catalytic activity, high selectivity, and high stability. Carbon-based materials, due to their abundant reserves, low cost, high conductivity, and stable electrochemical performance, hold broad application prospects in the electrocatalytic production of H2O2. However, existing carbon-based cathode catalysts still face the following technical challenges during long-term operation: First, the surface active sites of unmodified carbon materials are limited, hindering the development of 2e-… - ORR exhibits low selectivity and is prone to water generation via the four-electron pathway, resulting in suboptimal H2O2 yield. Secondly, carbon-based catalysts gradually undergo surface oxidation, structural degradation, and loss of active components during electrolysis, especially in acidic or alkaline electrolytes, where catalyst durability significantly decreases. Thirdly, the cathode is susceptible to flooding during long-term operation, hindering oxygen diffusion and mass transfer to the catalytically active sites, leading to a gradual decline in current efficiency.
[0004] To address the aforementioned issues, existing research has attempted to enhance the catalytic activity of carbon materials through heteroatom doping (such as nitrogen doping, sulfur doping, and oxygen doping). Furthermore, polymethylhydrosiloxane-modified gas diffusion electrodes, utilizing their superhydrophobic properties, can maintain high Faraday efficiency during long-term operation. However, current technologies lack a comprehensive modification scheme that simultaneously addresses the issues of catalytic activity, selectivity, and long-term durability. Single doping modifications or single hydrophobic modifications are insufficient to simultaneously improve catalytic performance and durability. More importantly, existing heteroatom doping modification processes generally rely on high-temperature heat treatment (typically above 600℃) to introduce heteroatoms. High-temperature processes not only consume enormous amounts of energy but also easily lead to changes in the graphitization degree of the carbon support, collapse of the pore structure, and excessive removal of surface oxygen functional groups, which weakens the intrinsic surface polarity of the carbon material and is detrimental to the uniform anchoring of the subsequent hydrophobic layer. Therefore, developing a catalyst preparation method that requires no high-temperature treatment throughout the process and gently constructs active sites and stable hydrophobic interfaces through chemical bonding is of great significance for achieving green manufacturing and synergistic performance improvement of electrosynthetic H2O2 catalysts. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a high-durability catalyst, its preparation method, and its applications. This invention, through a series of modification measures, synergistically improves durability and catalytic performance, overcoming the technical limitation of difficulty in simultaneously achieving activity, selectivity, and durability.
[0006] To achieve the above technical objectives, the technical solution adopted in the embodiments of the present invention is as follows: In a first aspect, embodiments of the present invention provide a method for preparing a high-durability catalyst, comprising the following steps: (1) The carbon-based support material is placed in solution A for liquid phase activation pretreatment. The treatment temperature is 40-70℃ and the treatment time is 1-8 hours. Then it is washed with deionized water until neutral and dried under low temperature vacuum to obtain activated carbon-based support. (2) The activated carbon-based support obtained in step (1) is uniformly dispersed in an organic solvent, and a chemical grafting agent containing heteroatom functional groups is added. The reaction is carried out at 20-100℃ for 2-24 hours under inert gas protection. After the reaction is completed, the carbon-based material is obtained by washing and centrifugation. (3) Disperse the heteroatom chemically grafted modified carbon-based material obtained in step (2) in a solution of hydrophobic modifier, and let it stand or stir to solidify at 15-60℃ for 0.5-24 hours; (4) The material obtained in step (3) is subjected to vacuum drying and stabilization treatment at 60-120℃ for 1-6 hours, and after natural cooling, the modified high-durability catalyst is obtained.
[0007] Further, in step (1), the carbon-based support material is selected from one or more of carbon black, activated carbon, carbon nanotubes, carbon fibers, graphene and mesoporous carbon; Solution A is selected from one or more mixed solutions of nitric acid, sulfuric acid, hydrogen peroxide solution, potassium permanganate solution and ammonium persulfate solution, with a concentration of 0.5-6 mol / L.
[0008] Furthermore, in step (1), the solid content is controlled at 0.5%-5% during liquid phase activation pretreatment, and the temperature of low-temperature vacuum drying is 30-60℃.
[0009] Further, in step (2), the organic solvent is selected from one or more of ethanol, isopropanol, N,N-dimethylformamide and tetrahydrofuran.
[0010] Further, in step (2), the chemical grafting agent is selected from one or more of the following: p-aminobenzenesulfonic acid, 3-aminopropyltriethoxysilane, polyethyleneimine, N,N-dicyclohexylcarbodiimide, aniline tetramer, mercaptoacetic acid, 2-mercaptobenzothiazole, cysteine, phytic acid, and phosphonic silane coupling agent. The mass ratio of the activated carbon-based support to the chemical grafting agent is 1:0.1-1.5.
[0011] Further, in step (3), the hydrophobic modifier is a room temperature curing hydrophobic agent that can be crosslinked and cured without high temperature sintering, and is selected from one or more of polymethylhydrosiloxane, methyltriethoxysilane, long-chain alkyltrichlorosilane, perfluorodecyltrimethoxysilane, and hydroxyl-terminated polydimethylsiloxane. The mass fraction of the hydrophobic modifier is 0.1%-15%.
[0012] Furthermore, the solvent of the hydrophobic modifier is selected from one or more of anhydrous ethanol, isopropanol, and n-hexane, and the system contains trace amounts of water to promote hydrolysis and condensation.
[0013] Secondly, embodiments of the present invention provide a high-durability catalyst, which is prepared using the preparation method described in the first aspect.
[0014] Thirdly, embodiments of the present invention provide the application of the high-durability catalyst described in the second aspect, wherein the high-durability catalyst is used in the electrochemical synthesis of hydrogen peroxide.
[0015] Furthermore, the high-durability catalyst is used as a cathode catalyst for the two-electron oxygen reduction reaction to electrosynthesize H2O2, with an operating voltage range of 0-0.8V (vs. RHE) and an electrolyte pH of 1-14.
[0016] The beneficial effects of the technical solution provided by the embodiments of the present invention are as follows: 1. This invention eliminates the need for high-temperature calcination throughout the entire process (the maximum temperature does not exceed 120℃), significantly reducing energy consumption during preparation. Simultaneously, the mild conditions perfectly preserve the original pore structure, high specific surface area, and intrinsic conductivity of the carbon support, avoiding the problems of carbon skeleton collapse and conductivity degradation at high temperatures.
[0017] 2. This invention utilizes liquid-phase chemical grafting to stably connect heteroatom functional groups to the carbon surface via covalent bonds. The active sites have a well-defined structure, uniform distribution, and controllable density. The grafted flexible molecular segments facilitate the formation of abundant solid-liquid-gas three-phase interfaces, significantly improving the 2e... - Intrinsic activity and selectivity of ORR.
[0018] 3. The room-temperature curing hydrophobic agent used in this invention can chemically crosslink with the grafted polar functional groups or form an interpenetrating network, making the hydrophobic layer less prone to peeling off. This chemically bonded hydrophobic interface has stronger durability than physical coating, and can continuously block electrolyte wetting during long-term electrolysis, effectively preventing catalyst flooding and loss of active components.
[0019] 4. The operating conditions of each step in this invention are mild, and the raw materials used are all common industrial products. No expensive equipment or special reaction conditions are required. The steps are well connected, making it suitable for continuous production and promising for industrial application.
[0020] 5. The high-durability catalyst prepared by this invention exhibits good catalytic activity and stability, can be adapted to different electrolyte systems, and has a wide range of applications. Attached Figure Description
[0021] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings.
[0022] Figure 1 This is a selectivity test chart of the modified high-durability catalyst prepared in Example 1 of the present invention.
[0023] Figure 2 This is a selectivity comparison curve of the catalysts prepared in Example 3 and Comparative Example 1 of the present invention.
[0024] Figure 3 This is a comparison chart of the yield of the cathode catalyst prepared in Example 4 of the present invention before and after 50 hours of durability testing. Detailed Implementation
[0025] In the description of this invention, it should be understood that the orientation or positional relationship indicated by directional terms such as "inner" and "outer", "upper" and "lower", "left" and "right" is usually based on the orientation or positional relationship shown in the accompanying drawings, and is only for the convenience of describing this invention and simplifying the description. Unless otherwise stated, these directional terms do not indicate or imply that the device or element referred to must have a specific orientation or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation on the scope of protection of this invention.
[0026] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0027] Example 1 A method for preparing a high-durability catalyst includes the following steps: (1) Take 5g of XC-72R carbon black and place it in 100mL of a 3mol / L mixed solution of nitric acid and sulfuric acid (volume ratio 1:1) for liquid phase activation pretreatment. Stir and oxidize it in a water bath at 70℃ for 4 hours. After cooling, wash it repeatedly with deionized water by centrifugation until the filtrate is neutral. Dry it overnight in a vacuum drying oven at 60℃ to obtain activated carbon black. (2) Take 3g of the above activated carbon black, ultrasonically disperse it in 100mL of anhydrous ethanol, and add 0.5g of p-aminobenzenesulfonic acid. Under nitrogen protection, the grafting reaction is carried out in a water bath at 60℃ for 8 hours. After the reaction is completed, wash repeatedly with deionized water and ethanol, centrifuge and dry at 60℃ to obtain benzenesulfonic acid-based grafted modified carbon black. (3) Disperse 2g of the above-mentioned grafted modified carbon black in a hexane solution containing 2wt% polymethylhydrosiloxane and let it stand at 25°C for 6 hours to cure. (4) The material obtained in step (3) is placed in a vacuum drying oven and dried and stabilized at 100°C for 4 hours. After natural cooling, the target modified high-durability cathode catalyst is obtained.
[0028] Electrochemical testing conditions: A three-electrode system was used in a constant-temperature five-necked flask at 25°C in a constant-temperature water bath. A PINE rotating disk electrode apparatus was used, employing a ring disk electrode and a reversible hydrogen electrode. The electrolyte was a 0.1 mol / L sodium sulfate solution saturated with oxygen and nitrogen. Prior to testing, activation was performed using cyclic voltammetry from 1.0 V to 0 V, with 100 activation cycles and a scan rate of 100 mV·s. -1 The test was performed using a linear voltammetric scan (LSV), scanning from 1.0V to 0V at a rotation speed of 1600 rpm and a scan rate of 10 mV·s. -1 The ring and disk currents saturated with nitrogen and oxygen, respectively, were collected, and the selectivity and yield after removing the nitrogen background were calculated. This was done in galvanostatic mode (100 mA / cm²).2 The stability test was conducted under the following conditions, and the durability test time for this invention was 50 hours.
[0029] Example 2 A method for preparing a high-durability catalyst includes the following steps: (1) Take 5g of carbon nanotubes and place them in 100mL of 2mol / L nitric acid solution for liquid phase activation pretreatment. Stir and oxidize them in a 70℃ water bath for 4 hours. After cooling, wash them repeatedly with deionized water until the filtrate is neutral. Dry them overnight in a vacuum drying oven at 60℃ to obtain activated carbon black. (2) Take 3g of the above activated carbon nanotubes, ultrasonically disperse them in 80mL of isopropanol, and add 0.8g of 3-aminopropyltriethoxysilane. Reflux the grafting reaction at 80℃ under nitrogen protection for 12 hours. After the reaction, wash repeatedly with deionized water and ethanol, centrifuge and dry at 60℃ to obtain grafted modified carbon nanotubes. (3) The above-mentioned grafted modified carbon nanotubes were dispersed in an ethanol solution (containing 1% water) containing 3wt% perfluorodecyltrimethoxysilane and stirred and cured at 40°C for 10 hours. (4) The material obtained in step (3) is vacuum dried and stabilized at 110°C for 3 hours, and the target catalyst is obtained after natural cooling.
[0030] The electrochemical testing conditions were the same as in Example 1.
[0031] Example 3 A method for preparing a high-durability catalyst includes the following steps: (1) Take 5g of mesoporous carbon and place it in 100mL of 4mol / L nitric acid solution for liquid phase activation pretreatment. Stir and oxidize it in a 70℃ water bath for 5 hours. After cooling, wash it repeatedly with deionized water until the filtrate is neutral. Dry it overnight in a vacuum drying oven at 30℃ to obtain activated mesoporous carbon. (2) Take 3g of activated mesoporous carbon, ultrasonically disperse it in 100mL of ethanol, add 0.6g of phytic acid and 0.2g of p-aminobenzenesulfonic acid, and reflux the grafting reaction at 90℃ for 6 hours under nitrogen protection. After the reaction, wash repeatedly with deionized water and ethanol, and dry at 60℃ to obtain phosphorus / nitrogen co-grafted modified mesoporous carbon. (3) Disperse 1g of the above phosphorus / nitrogen co-grafted modified mesoporous carbon in a hexane solution (100mL) containing 1.5wt% octadecyltrichlorosilane, add 3mL of deionized water, and let it stand at 25℃ for 8 hours to self-assemble. (4) The material obtained in step (3) is vacuum dried and stabilized at 80°C for 6 hours, and the target catalyst is obtained after natural cooling.
[0032] The electrochemical testing conditions were the same as in Example 1.
[0033] Example 4 A method for preparing a high-durability catalyst includes the following steps: (1) Take 5g of carbon nanotubes and place them in 100mL of a 2.5mol / L mixed solution of nitric acid and sulfuric acid (volume ratio 3:1) for liquid phase activation pretreatment. Stir and oxidize them in a water bath at 70℃ for 4 hours. After cooling, wash them repeatedly with deionized water until the filtrate is neutral. Dry them overnight in a vacuum drying oven at 30℃ to obtain activated carbon nanotubes. (2) Take 3g of activated carbon nanotubes, ultrasonically disperse them in 100mL of ethanol, add 1.2g of polyethyleneimine and 0.2g of N,N-dicyclohexylcarbodiimine, and reflux the grafting reaction at 75℃ for 14 hours under nitrogen protection. After the reaction is completed, wash repeatedly with deionized water and ethanol, and dry at 60℃ to obtain grafted modified carbon nanotubes. (3) The above-mentioned grafted modified carbon nanotubes were dispersed in an ethanol / water mixed solution containing 2wt% methyltriethoxysilane (100mL, ethanol to deionized water volume ratio 9:1) and stirred and cured at 35°C for 10 hours. (4) The material obtained in step (3) is vacuum dried and stabilized at 100°C for 5 hours, and the target catalyst is obtained after natural cooling.
[0034] The electrochemical testing conditions were the same as in Example 1.
[0035] Comparative Example 1 The difference between this comparative example and Example 3 is that the chemical grafting heteroatom doping modification in step (2) is not performed, but only the activation pretreatment in step (1), the hydrophobic modification in step (3), and the low-temperature stabilization posttreatment in step (4) are performed.
[0036] The electrochemical testing conditions were the same as in Example 1.
[0037] Comparative Example 2 The difference between this comparative example and Example 4 is that the surface hydrophobic modification in step (3) is not performed, but only the activation pretreatment in step (1), the chemical grafting heteroatom doping modification in step (2), and the low-temperature stabilization posttreatment in step (4) are performed.
[0038] The electrochemical testing conditions were the same as in Example 1.
[0039] Table 1. Comparison of performance and durability of catalysts in each example and comparative example. As shown in Table 1, the H2O2 selectivity of Examples 1-4 of the present invention (89%-92%) is significantly better than that of Comparative Example 1 (65%) without heteroatom grafting modification, indicating that chemical grafting of heteroatom functional groups effectively improves 2e-E.- The selectivity of ORR. The 50-hour yield retention rate (89%-96%) of Examples 1-4 of this invention is significantly better than that of Comparative Example 2 (62%) without hydrophobic modification, indicating that the chemically bonded hydrophobic layer effectively improves the long-term operational durability of the catalyst. In addition, the highest temperature of the preparation methods in Examples 1-4 of this invention does not exceed 120°C, realizing a completely high-temperature-free green preparation, and different carbon-based supports (carbon black, carbon nanotubes, mesoporous carbon, graphene) can all achieve performance improvement through the all-liquid-phase chemical modification strategy of this invention, verifying the universality of the method of this invention.
[0040] Figure 1 The graph shows the selectivity for hydrogen peroxide production at different potentials, calculated from the rotating ring electrode test of the modified high-durability cathode catalyst prepared in Example 1 of this invention in 0.1 mol / L KOH electrolyte. The horizontal axis represents potential E (vs. RHE) in V, and the vertical axis represents the selectivity for hydrogen peroxide production (H2O2%). As can be seen from the graph, the ring current remains high across a wide potential range from 0 V to 0.6 V (vs. RHE), and the H2O2 selectivity calculated by the RRDE method remains stable above 90% in the 0-0.6 V potential range.
[0041] from Figure 2 It can be seen that without chemical grafting heteroatom doping modification, the selectivity is significantly reduced. This result indicates that the catalyst of this invention has high selectivity for the two-electron oxygen reduction pathway, far superior to Comparative Example 1 (selectivity of only 65%) without heteroatom grafting, proving that chemically grafted heteroatom functional groups have a high selectivity for 2e-electron oxygen reduction. - ORR selectivity has a decisive effect on improvement.
[0042] Figure 3 The cathode catalyst prepared in Example 4 of this invention was tested in constant current mode (100 mA / cm²). 2 The curves showing the decline in H2O2 yield after 50 hours of continuous operation are shown. As can be seen from the figure, the catalyst prepared in Example 4 can produce approximately 554 mmol of hydrogen peroxide per hour per gram of catalyst. After 50 hours of operation, the yield of the catalyst at a potential of 0.4V remains at 96% of the initial value, with a gradual decline and no sudden drop, demonstrating excellent long-term operational stability.
[0043] Meanwhile, as shown in Table 1, the catalyst in Comparative Example 2 exhibited a significant yield decline within the first 50 hours, with a yield retention rate of only 62%. The comparison of retention rate data indicates that surface hydrophobic modification plays a crucial role in suppressing the erosion of active sites by the electrolyte and preventing catalyst flooding. The chemically bonded hydrophobic layer effectively ensures the structural integrity and catalytic activity of the catalyst during long-term electrolysis.
[0044] Finally, it should be noted that the above specific embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A method for preparing a high-durability catalyst, characterized in that, Includes the following steps: (1) The carbon-based support material is placed in solution A for liquid phase activation pretreatment. The treatment temperature is 40-70℃ and the treatment time is 1-8 hours. Then it is washed with deionized water until neutral and dried under low temperature vacuum to obtain activated carbon-based support. (2) The activated carbon-based support obtained in step (1) is uniformly dispersed in an organic solvent, and a chemical grafting agent containing heteroatom functional groups is added. The reaction is carried out at 20-100℃ for 2-24 hours under inert gas protection. After the reaction is completed, the carbon-based material is obtained by washing and centrifugation. (3) Disperse the heteroatom chemically grafted modified carbon-based material obtained in step (2) in a solution of hydrophobic modifier, and let it stand or stir to solidify at 15-60℃ for 0.5-24 hours; (4) The material obtained in step (3) is subjected to vacuum drying and stabilization treatment at 60-120℃ for 1-6 hours, and after natural cooling, the modified high-durability catalyst is obtained.
2. The method for preparing the high-durability catalyst according to claim 1, characterized in that, In step (1), the carbon-based support material is selected from one or more of carbon black, activated carbon, carbon nanotubes, carbon fibers, graphene and mesoporous carbon; Solution A is selected from one or more mixed solutions of nitric acid, sulfuric acid, hydrogen peroxide solution, potassium permanganate solution and ammonium persulfate solution, with a concentration of 0.5-6 mol / L.
3. The method for preparing the high-durability catalyst according to claim 1, characterized in that, In step (1), the solid content is controlled at 0.5%-5% during liquid phase activation pretreatment, and the temperature of low-temperature vacuum drying is 30-60℃.
4. The method for preparing the high-durability catalyst according to claim 1, characterized in that, In step (2), the organic solvent is selected from one or more of ethanol, isopropanol, N,N-dimethylformamide and tetrahydrofuran.
5. The method for preparing the high-durability catalyst according to claim 1, characterized in that, In step (2), the chemical grafting agent is selected from one or more of the following: p-aminobenzenesulfonic acid, 3-aminopropyltriethoxysilane, polyethyleneimine, N,N-dicyclohexylcarbodiimide, aniline tetramer, mercaptoacetic acid, 2-mercaptobenzothiazole, cysteine, phytic acid, and phosphonic silane coupling agent. The mass ratio of the activated carbon-based support to the chemical grafting agent is 1:0.1-1.
5.
6. The method for preparing the high-durability catalyst according to claim 1, characterized in that, In step (3), the hydrophobic modifier is a room temperature curing hydrophobic agent that can be crosslinked and cured without high temperature sintering, and is selected from one or more of polymethylhydrosiloxane, methyltriethoxysilane, long-chain alkyltrichlorosilane, perfluorodecyltrimethoxysilane, and hydroxyl-terminated polydimethylsiloxane. The mass fraction of the hydrophobic modifier is 0.1%-15%.
7. The method for preparing the high-durability catalyst according to claim 1 or 6, characterized in that, The solvent of the hydrophobic modifier is selected from one or more of anhydrous ethanol, isopropanol, and n-hexane, and the system contains trace amounts of water to promote hydrolysis and condensation.
8. A highly durable catalyst, characterized in that, It is prepared by the preparation method according to any one of claims 1-6.
9. The application of the high-durability catalyst according to claim 8, characterized in that, The high-durability catalyst is used in the electrochemical synthesis of hydrogen peroxide.
10. The application of the high-durability catalyst according to claim 9, characterized in that, The high-durability catalyst is used as a cathode catalyst for the electrosynthesis of H2O2 via a two-electron oxygen reduction reaction, with an operating voltage range of 0-0.8V (vs. RHE) and an electrolyte pH of 1-14.